Non-invasive Global and Regional Myocardial Work Predicts High-Risk Stable Coronary Artery Disease Patients With Normal Segmental Wall Motion and Left Ventricular Function - Zhang, Jun; Liu, Yani; Deng, Youbin; Zhu, Ying; Sun, Ruiying; Lu, Shirui (Frontiers in Cardiovascular Medicine, 2021)
Background: Previous studies suggested that myocardial work (MW) may identify abnormalities in the left ventricular (LV) function and establish a more sensitive index for LV dysfunction at the early stage. This study aimed to explore the value of global and regional MW parameters in predicting high-risk stable coronary artery disease (SCAD) patients with normal wall motion and preserved LV function. Patients and Methods: A total of 131 patients, who were clinically diagnosed as SCAD with normal wall motion and LV function, were finally included in this study. Global MW parameters, including global work index (GWI), global constructive work (GCW), global waste work (GWW), and global work efficiency (GWE) were measured with non-invasive LV pressure-strain loops constructed from speckle-tracking echocardiography. Regional myocardial work index (RWI) and work efficiency (RWE) were also calculated according to the perfusion territory of each major coronary artery. All patients underwent coronary angiography and were divided into the high-risk SCAD group, the non-high-risk SCAD group, and the No SCAD group according to the range and degrees of coronary arteries stenosis. Results: The global longitudinal strain (GLS), GWI and GCW were statistically different (P < 0.001) among the three groups. In the high-risk SCAD group, GLS, GWI, and GCW were significantly lower than the other two groups (P < 0.05). Receiver operating characteristic analysis demonstrated GWI and GCW could predict high-risk SCAD at a cutoff value of 1,808 mm Hg% (sensitivity, 52.6%; specificity, 87.8%; predictive positive value, 76.3%; predictive negative value, 69.9%) and 2,308 mm Hg% (sensitivity, 80.7%; specificity, 64.9%; predictive positive value, 63.3%; predictive negative value, 80.0%), respectively. Multivariate analyses showed that carotid plaque, decreased GWI, and GCW was independently related to high-risk SCAD. The cutoff values of RWILAD, RWILCX, and RWIRCA were 2,156, 1,929, and 1,983 mm Hg% in predicting high-risk SCAD, respectively (P < 0.001). When we combined RWI in two or three perfusion regions, the diagnostic performance of SCAD was improved (P < 0.001). Conclusions: Both global and regional MW parameters have great potential in non-invasively predicting high-risk SCAD patients with normal wall motion and preserved LV function, contributing to the early identification of high-risk patients who may benefit from revascularization therapy.